Basaltic and Solution Reference Materials for Iron, Copper and Zinc Isotope Measurements. Issue 1 (23rd October 2018) - Li, Jin; Tang, Suo‐han; Zhu, Xiang‐kun; Li, Zhi‐hong; Li, Shi‐Zhen; Yan, Bin; Wang, Yue; Sun, Jian; Shi, Yao; Dong, Aiguo; Belshaw, Nick S.; Zhang, Xingchao; et al.
Abstract : Iron, Cu and Zn stable isotope systems are applied in constraining a variety of geochemical and environmental processes. Secondary reference materials have been developed by the Institute of Geology, Chinese Academy of Geological Sciences (CAGS), in collaboration with other participating laboratories, comprising three solutions (CAGS‐Fe, CAGS‐Cu and CAGS‐Zn) and one basalt (CAGS‐Basalt). These materials exhibit sufficient homogeneity and stability for application in Fe, Cu and Zn isotopic ratio determinations. Reference values were determined by inter‐laboratory analytical comparisons involving up to eight participating laboratories employing MC‐ICP‐MS techniques, based on the unweighted means of submitted results. Isotopic compositions are reported in per mil notation, based on reference materials IRMM‐014 for Fe, NIST SRM 976 for Cu and IRMM‐3702 for Zn. Respective reference values of CAGS‐Fe, CAGS‐Cu and CAGS‐Zn solutions are as follows: δ 56 Fe = 0.83 ± 0.07 and δ 57 Fe = 1.20 ± 0.13, δ 65 Cu = 0.57 ± 0.06, and δ 66 Zn = −0.79 ± 0.12 and δ 68 Zn = −1.65 ± 0.24, respectively. Those of CAGS‐Basalt are δ 56 Fe = 0.15 ± 0.07, δ 57 Fe = 0.22 ± 0.10, δ 65 Cu = 0.12 ± 0.08, δ 66 Zn = 0.17 ± 0.13, and δ 68 Zn = 0.34 ± 0.26 (2 s ). Key Points: Three reference solutions (CAGS‐Fe, CAGS‐Cu and CAGS‐Zn) and one basalt reference material (CAGSR) for calibrating Fe, Cu and Zn isotope ratio measurements have been developed. CAGS‐Fe, CAGS‐Cu, CAGS‐Zn and CAGSR show sufficient homogeneity and stability. Recommended reference values were determined by inter‐laboratory comparison of results from participating laboratories.